Elucidation of a Novel Role of YebC in Surface Polysaccharides Regulation of Escherichia coli bipA-Deletion - Choi, Eunsil; Jeon, Hyerin; Oh, Changmin; Hwang, Jihwan (Frontiers in Microbiology, 2020)
The BipA (BPI-inducible protein A) protein is ubiquitously conserved in various bacterial species and belongs to the translational GTPase family. Interestingly, the function of Escherichia coli BipA is not essential for cell growth under normal growth conditions. However, cultivation of bipA-deleted cells at 20°C leads to cold-sensitive growth defect and several phenotypic changes in ribosome assembly, capsule production, and motility, suggesting its global regulatory roles. Previously, our genomic library screening revealed that the overexpressed ribosomal protein (r-protein) L20 partially suppressed cold-sensitive growth defect by resolving the ribosomal abnormality in bipA-deleted cells at low temperature. Here, we explored another genomic library clone containing yebC, which encodes a predicted transcriptional factor that is not directly associated with ribosome biogenesis. Interestingly, overexpression of yebC in bipA-deleted cells diminished capsule synthesis and partially restored lipopolysaccharide (LPS) core maturation at a low temperature without resolving defects in ribosome assembly or motility, indicating that YebC may be specifically involved in the regulation of exopolysaccharide and LPS core synthesis. In this study, we collectively investigated the impacts of bipA-deletion on E. coli capsule, LPS, biofilm formation, and motility and revealed novel roles of YebC in extracellular polysaccharide production and LPS core synthesis at low temperature using this mutant strain. Furthermore, our findings suggest that ribosomal defects as well as increased capsule synthesis, and changes in LPS composition may contribute independently to the cold-sensitivity of bipA-deleted cells, implying multiple regulatory roles of BipA.